The Effect of Emotional Intelligence On Employee Performance Of Pt. Plastik Karawang Flexindo - Neneng Lely Amelia; Sonny Hersona; Hawignyo (Institute of Computer Science (IOCS), 2022)
This study aims to determine: (i) Emotional intelligence at PT. Plastics Karawang Flexindo (ii) Employee performance at PT. Plastics Karawang Flexindo and (iii) the influence of emotional intelligence on employee performance at PT. Plastic Karawang Flexindo. This research method uses a quantitative approach. The study used a survey method through a questionnaire. How to collect data by using a questionnaire and observation. The data collected is questionnaire data from 123 respondents of PT.Plastik Karawang employees and the techniques used in determining random samples or random samples, mixed samples. Testing technique The hypothesis of this research is how much influence the emotional influence on the performance of PT.Plastik Karawang Flexindo employees. The results showed that emotional intelligence has a significant influence on employee performance, 41.2% the rest is influenced by other factors and outside the company's environment. The author suggests to the relevant parties, namely: (i) There is a strong and significant relationship between emotional intelligence and employee performance, the author suggests that apart from prioritizing intelligence, the company also needs to pay attention to emotional intelligence so that there is a balance in good performance. (ii) Companies need to improve performance by means of periodic evaluations with the aim of the company having an overview of employee performance that needs to be improved so that performance increases and (iii) It is hoped that similar research will be carried out to find out factors other than emotional intelligence that can affect performance so that it can be identified. how much contribution is given to employee performance.